A case study of the Buklat - Aklat mobile library - Santiago, Glori Stephanie Rossini S.; Sison, Josephine C. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2002)
This thesis was undertaken for the purpose of determining how effective the "bookmobile" concept is in providing information to diversified people. It also sought to recommend solutions to problems of the bookmobiles as an approach to contributing knowledge to different user groups.
Although the bookmobile concept started in the United States, our very own National Bookstore introduced the Mobile Library approach to information provision through the program "Buklat -Aklat Mobile Library." This program aims to give the best and the widest selection of reading materials to students in public schools and barangays. Buklat - Aklat Mobile Library serves as a link in bridging the gap between ignorance and knowledge among the youth.
Other bookmobile groups like for instance the one by the Museo Pambata Foundation Inc. aims to revive our rich cultural heritage using the bookmobile as a tool for exploring other learning opportunities for children and students. Other programs like Aklat KKK also aims to serve depressed areas in Manila. This program teaches Filipino children the value and power of reading in their daily lives and how to apply what they read for improving their way of life.
Of the two trips participated, 100 questionnaires were sent and collected in Holy Angel University in Angeles City, Pampanga, and 100 questionnaires were also sent and collected from Cainta Elementary School for a total of 200 respondents.
This study was conducted through the use of questionnaires and interviews of the mobile librarians as well as the users of the mobile library service, and a participatory observation was undertaken.
As a result, children find the mobile library important in their education. The mobile library caters only schools/campuses to elementary level aged 5-12 yr. old. Filipiniana books were mostly used in the library. No adult books, magazines, and newspapers available.
The mobile library have 200 + titles in the collection; books are mostly soft bound, sixty percent (60) locally produced and forty percent (40) foreign.
Indeed, this mobile library program is a very tool in information dissemination to many people. However, it is better if the Buklat - Aklat Mobile Library have proper budgets to sustain the program. Also, government agencies like Department of Education, Culture and Sports (DECS) or other private institutions should support this kind of program.
And to everybody who wants to improve one's life, be a sponsor, donor, or a volunteer in this project. Let us help children to follow their dreams.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Bookmobiles -- Philippines; Children -- Services for -- Philippines